Strategi Guru dalam Membentuk Kepribadian Anak (Studi Pada PAUD Al-Khairaat Kec. Lore Selatan Kab. Poso) - Pettalongi, Adawiyah (Musawa: Journal for Gender Studies, 2023)
Implementation strategy for the formation of children’s personality in PAUD Alkhairaat Kec. South Lore Kab. Poso uses two approaches, namely the intervention process in this case the teacher’s participation and habituation with character development. The intervention process is developed and implemented through teaching and learning activities that are deliberately designed to achieve character building goals through the implementation of various structured activities. Meanwhile, various situations and conditions are created and grown through a habituation process, which contains various reinforcements that enable students at school, at home, and in their community to adapt to behave according to the expected values.